FOPID controlled PV based QBC fed gamma Z-source inverter applicable for pump operations in an induction motor drive - Selvaraj, Krishnan; David, Anbarasi Jebaselvi Gnanaiah; Sathi, Rama Reddy; Kuppusamy, Pradeepa (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
A closed loop current mode-fractional-order-PID (CM-FOPID) controlled and PV based quadratic-boost-converter (QBC) fed gamma Z-Source Inverter with Induction motor system (PV-QBC-GZSI-IMS) for pump operation is proposed here. This work recommends a combination of QBC with gamma Z-source-inverter between the DC link source and asynchronous motor system. This will reduce the voltage rating of PV panel and its initial cost. GZSI reduces the current spikes in stator current. The objective of this research work is to regulate the speed of PV-QBC-GZSI-IMS. This effort deals with the closed loop response of PV-QBC-GZSI-IMS accompanied by current-mode-proportional integral (CM-PI) and CM-FOPID controllers. The performance investigations are analyzed with the control of QBC fed Gamma Z-source inverter with motor load using CM-PI and CM-FOPID controllers and the detailed comparison has been presented. MATLAB/Simulink outputs obtained with their respective speed and torque characteristics in time domain have been depicted. The closed loop CM-FOPID control of PV-QBC-GZSI-IMS is superior to the closed loop CM-PI control of PV-QBC-GZSI-IMS. The proposed QBC-converter reduces the voltage rating of PV panel and GZSI reduces current spikes in motor. The novelty of the article is to enhance the dynamic response of PV-QBC-GZSI-IMS using FOPID. The steady state error in torque is reduced to 0.52 N-m using FOPID.